Pengaruh Iklim Dan Budaya Organisasi Terhadap Inovasi Pegawai Di Lingkungan Biro Hukum Kementerian Keuangan - Zachroni; Noor Syaifudin; Nurhasanah (Coopetition : Jurnal Ilmiah Manajemen, 2021)
Along with developments and the demands of the situation, the work can be done not merely as business as usual, but needs to prioritize quality, effectiveness, and efficiency through innovation. These innovations can be created with the support of an organizational climate and good organizational culture. This study aims to determine the influence of climate and organizational culture, both partially and simultaneously on employee innovation, especially within the Legal Bureau of Ministry of Finance (MoF). The population in this study were employees in the Legal Bureau of Ministry of Finance, totaling 136 people. The research sample is determined by the survey method, meaning that all members of the population are sampled. This research is quantitative descriptive. The variables studied included the independent variables in the form of organizational climate and organizational culture and the dependent variables in the form of employee innovation. Research data obtained through the distribution of questionnaires. The data obtained were processed using Statistical Product and Services Solution version 18 (SPSS 18) software. The results showed that the organizational climate partially influences employee innovation. Likewise, organizational culturepartially influences employee innovation. Simultaneously, organizational climate and organizational culture influence employee innovation